Receptor-mediated cell mechanosensing - Yunfeng Chen; Lining Arnold Ju; Muaz Nik Rushdi; Chenghao Ge; Cheng Zhu (2017)
Mechanosensing describes the ability of a cell to sense mechanical cues of its microenvironment, including not only all components of force, stress, and strain but also substrate rigidity, topology, and adhesiveness. This ability is crucial for the cell to respond to the surrounding mechanical cues and adapt to the changing environment. Examples of responses and adaptation include (de)activation, proliferation/apoptosis, and (de)differentiation. Receptor-mediated cell mechanosensing is a multistep process that is initiated by binding of cell surface receptors to their ligands on the extracellular matrix or the surface of adjacent cells. Mechanical cues are presented by the ligand and received by the receptor at the binding interface; but their transmission over space and time and their conversion into biochemical signals may involve other domains and additional molecules. In this review, a four-step model is described for the receptor-mediated cell mechanosensing process. Platelet glycoprotein Ib, T-cell receptor, and integrins are used as examples to illustrate the key concepts and players in this process.